Mousikê concepção de conhecimento da república V-VII - Siqueira, Sávio Lima (2015)
We analyzed the mousikê (Mουσικὴ) in analogy of the line of platonic knowledge from book VI of the Republic, and in which the intelligible region is located: in Dianoia (διάνοια) or Noesis (νόησις). We talk about the mousikê in the construction of pólis, the confirmation of the insuficience of its teaching on defining justice until its didactic role, which causes to maintain it in education. We also point the critic at the mimésis and all poetic arts, for its distance from the intelligible domain, and the censorship of poets and their representations and the need for their surveillance. We evaluated the mimesis in the mousikê, summarizing the representations that are mimetic arts; the reception to this mimesis, imitation and representation, arguing against the amadores de espetáculos, in book V of the Republic. We found the location of mousikê in intelligible, in the analogy of the line, in Book VI of the República, to the assessment of four cognitive operations presented by Plato. We observed the mousikê as knowledge in Book VII of the Republic, and its role among the other propaedeutic science of dialectics, without realizing what we consider a Pythagorean interpretation of mousikê. The focus of this work is to draw attention to the four cognitive operations of the soul (Rep.511d): Intelligence, Noesis (νόησις), Understanding, Dianoia (διάνοια), Belief, Pistis (pίstis) and Assumption, in the Imaginário (eἰkasίa). We traveled the analyzes by expert researchers as a way to confront our thesis, based on what is written in the Republic. In our interpretation, which is not performed in a Pythagorean way, Plato speaks only of two cognitive operations, not two songs. The only possible location of the mousikê in the Analogy of the Line is in Dianoia, along with other propaedeutical subjects of the Dialectic. In Noesis can only be the dialectic as the summit of science, according to the República. The mousikê cannot find at the apex of the filósofo-rei studies.